RELIGIOUS TOLERANCE IN ISLAM - Sherzodjon Umaraliyev (International Journal of Literature and Language Studies, 2026)
This article analyzes the manifestation of the principles of religious tolerance within the primary sources of Islam—namely, the Quran and the Hadith. It explores historical exemplars of tolerance demonstrated during the life and prophetic mission of Prophet Muhammad (peace be upon him), as well as the governance, decisions, and daily practices established by the Companions (Sahaba) and the Successors (Tabi'un). Furthermore, the paper provides a theological and legal analysis of contemporary fatwas governing peaceful coexistence and solidarity with non-Muslims in shared societies.